How do housing and labour markets affect individual homelessness?. Issue 7 (9th August 2019) - Johnson, Guy; Scutella, Rosanna; Tseng, Yi-Ping; Wood, Gavin
Abstract: We examine the impact of housing and labour market conditions on individual risks of homelessness. Our innovation is a focus on homelessness entries, although findings from jointly estimated homelessness entry and exit probit equations are reported. Risky behaviours and life experiences such as regular use of drugs, the experience of violence and biographies of acute disadvantage lead to a higher risk of becoming homeless. Public housing is a strong protective factor. We find clear evidence that for certain subgroups it is being the 'wrong person in the wrong place' that matters most when considering risks of entering homelessness. Indigenous Australians, for example, are no more likely to become homeless than other vulnerable groups holding housing and labour market conditions constant. However, tighter housing markets and weaker labour markets expose Indigenous Australians to significantly higher risks of entering homelessness.